The Impact of Perception of CSR on Purchase Intention with Mediating Role of Loyalty and Trust - Li, Haobo (2022)
In the era of economic globalization, with the progress of society and the intensification of competition among enterprises, taking corresponding responsibilities to relevant stakeholders and strengthening corporate social responsibilities are becoming the new trend of modern corporate philosophy. China's dairy production and per capita consumption have increased substantially, but in recent years, a series of dairy safety problems have weakened consumers' confidence. Chinese consumers expect to buy safe and reliable dairy products and hope for dairy companies that are more capable of undertaking corporate social responsibility. The purpose of this study is to examine the impact of consumers’ perception of CSR in China’s dairy industry on purchase intention and the mediating role of consumer trust and consumer loyalty. A survey methodology with quantitative data analysis was used. 218 valid questionnaires were collected online, and the data was analyzed via SPSS software. The empirical results of this study reveal that perception of CSR has positive influence on consumers’ purchase intention, and trust and loyalty both have mediating effect on perception of CSR and consumers’ purchase intention. The findings provide some management implications for dairy enterprises such as implementing diversified CSR activities, enhancing publicity, avoiding greenwashing, and insisting on long-term CSR strategy. Limitations and further research are also discussed.